Profil Kemampuan Koneksi Matematis Siswa SMK dalam Memecahkan Masalah Berdasarkan Polya Ditinjau dari Gender - Riska Riski; Sukayasa Sukayasa; Nurhayadi Nurhayadi (Jurnal Kreatif Online, 2022)
The purpose of this study was to describe the profile of the mathematical connection abilities of vocational high school students in solving mathematical problems based on Polya's steps in terms of gender. This study uses a qualitative descriptive approach that is in accordance with Polya's steps. The results showed that the profiles of male and female students' mathematical connection abilities in solving mathematical problems based on Polya's steps, namely (1) the stage of understanding the problem, students understand and identify facts, concepts by associating available information such as things that are known and asked about problems in other fields of study as well as writing down the information known and asked in full in the form of sentences, pictures and mathematical symbols; (2) the stage of making plans, students reveal about the steps of solving the problem of system of linear equation with two variables that will be used to solve problems regularly and precisely, using one method in solving problems; (3) the stage of carrying out the plan, students use the relationship between facts, concepts, mathematical principles on problems that will be solved properly; and (4) the re-examining stage, students recalculate the results obtained so that the test results obtained are the same as the results obtained at the beginning.